Research Progress on The Application of Nitrogen-Doped Three-Dimensional Graphene Hydrogels in Water Environment Pollution Remediation - Li, Tingjie (International Journal of Natural Resources and Environmental Studies, 2024)
With the rapid development of the chemical industry, a large amount of industrial wastewater is also produced, which contains a large amount of organic matter with high chemical stability and difficult to be biodegraded, such as acids, alkalis, salts, organic solvents, toxic dyes and heavy metal ions, which is very detrimental to the protection of natural ecology and the maintenance of human health. As a two-dimensional material, graphene's sp2 hybridized carbon atomic structure can produce π-π interactions with organic dye pollutants containing benzene ring structures, thereby adsorbing pollutants. Assembling two-dimensional graphene into a hydrogel with a three-dimensional network structure can further increase the contact area with pollutants and improve the adsorption of pollutants. This paper mainly discusses the research progress of the application of nitrogen-doped three-dimensional graphene hydrogels (NGHs) in water environment pollution remediation.